Dopamine triggers TOR signaling cascade to drive biomass and astaxanthin hyperaccumulation in Haematococcus lacustris under coordinated salinity and gradient light stress - Shiyu Lin; Qingwei Wang; Raoqiong Che; Qingqing Li; Chunli Yu; Min Yang; Lifang Li; Penghua Gao; Ying Qi; Feiyan Huang; Xiang Wang; Yongteng Zhao; et al. (Bioresource Technology, 2026)

Rheology-computational fluid dynamics co-regulation and experimental validation of coaxial three-dimensional printing - Jinjin Huang; Min Zhang; Arun S. Mujumdar; Chunli Li; Jiacong Lin; Jingyuan Li (Journal of Food Engineering, 2026)

Transcriptomic and proteomic analysis of MVK variant sites in two subtypes of porokeratosis - Shuqin Lai; Wenjie Zhu; Chunli Lin; Zimeng Guo; Shiqi Chen; Lang Xie; Jie Liu; Zhaolin Zeng; Cong You; Longnian Li (Journal of Applied Genetics, 2026)

Pollution Characteristics, Potential Sources and Transport Pathways of O3 and VOCs in a Coastal City of East China - Yuan Xue; Yufei Ling; Lei Tong; Jiayong Feng; Huan Lin; Chunli Liu; Cenyan Huang; Hang Xiao (Bulletin of Environmental Contamination and Toxicology, 2026)

Engineering a temperature-programmable biosensor toolkit for recombinant protein production in Corynebacterium glutamicum - Haofei Xu; Yanbo Li; Yiran Gan; Songzhou Liu; Bin Lin; Shijun Cen; Yankun Yang; Chunli Liu; Xiuxia Liu; Zhonghu Bai (Systems Microbiology and Biomanufacturing, 2026)

Environmental PET-microplastic exposure and risk of non-alcoholic fatty liver disease: An integrated computational toxicology and multi-omics study - Yu Yuan; Chunli Lin; Tianyu Zhang; Chao Song; Yuewen Sun; Hongzhen Tang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Feasibility of a Multi-Laboratory Model of Middle Cerebral Artery Thromboembolic Stroke with Thrombolysis: TE-MCAo - Michelle Lin; Mozammel Bhuiyan; Carly McCurry; Jessica Lamb; Marcio A. Diniz; Karni Bedirian; Anil K. Chauhan; Abhishek Jha; Aditi Jain; Enrique C. Leira; Rakeshkumar Patel; Mohammad B. Khan; et al. (Translational Stroke Research, 2026)
No single animal stroke model satisfies all needs of translational stroke investigation. While the nylon filament model is widely accepted in preclinical translational stroke research, thromboembolic models have more physiological relevance. Thromboembolic models are technically difficult, time consuming, and show variable results, making them problematic for multi-laboratory preclinical network use. We sought to develop and validate a multi-laboratory thromboembolic middle cerebral artery occlusion model that encompasses vessel occlusion and subsequent thrombolysis. To reduce the numbers of donor animals used, we developed a method to store donor blood for later use. Using prefabricated microcatheters, we simplified thrombus preparation and handling. Emboli were prepared in microcatheters and injected directly into the middle cerebral artery from the internal carotid artery. For thrombolysis we used intravenous Tenecteplase dosing at 1.5 mg/kg. To demonstrate feasibility and ease-of-use, the model was implemented at six research laboratories. We wrote and field-tested standard operating procedures, training videos, and hands-on surgical training workshops. We enrolled 170 Sprague Dawley rats of both sexes at six laboratories who performed 4 to 6 thrombus embolizations per week. All sites could achieve reproducible occlusion and thrombolysis. Thromboemboli prepared from stored blood served as well as emboli from freshly drawn blood. Of 135 rats who received one embolus, 33 (24%) died before 48-hour MRI scan. In survivors, stroke volume was 13 ± 16% of the ipsilateral hemisphere. Occlusions were seen in the MCA in 15%, distal ICA in 19%, both (T-occlusions) in 2% and in the MCA/ACA in 1%. Corner test, neurobehavioral battery, and MRI showed reasonably consistent stroke injury. We established the feasibility and reproducibility of a multi-laboratory rodent thromboembolic model but further development is needed to improve the success rate and lower the mortality rate before this model can be accepted widely.

A synthetic biocontrol consortium of Streptomyces salinarius and Bacillus halotolerans exhibits superior protection against Fusarium oxysporum infection in Pinus via synergistic interactions - Haixia Wang; Lin Fu; Chunli Li; Xuanyi Meng; Siyang Wang; Xinlu Zhang; Xinyu Zhou; Xiangna Wang; Fangliang Zheng; Chunyu Zhu (Plant and Soil, 2026)

Optimizing soil microbial functions under long-term straw return enhances nutrient acquisition, thereby improving nutrient availability and crop productivity in tobacco–rice rotation systems of southern China - Bianhong Zhang; Rikun Li; Zhicheng Chen; Chunli Zeng; Songquan Liao; Yazhou Liu; Ting Cheng; Yifei Liu; Lina Tang; Wenxiong Lin; Jinwen Huang (Agriculture, Ecosystems & Environment, 2026)

Improvement of Lactiplantibacillus plantarum stability and quality of 3D-printed brown rice by chickpea protein and fenugreek gum stabilized Pickering emulsions - Jinjin Huang; Min Zhang; Chung Lim Law; Chunli Li; Jiacong Lin (Food Chemistry, 2025)

Enhancing the stability of quercetin by loading into dual-layered hydrogel-emulsion gel using coaxial 3D food printing - Min Feng; Min Zhang; Arun S. Mujumdar; Chunli Li; Jiacong Lin (Innovative Food Science & Emerging Technologies, 2025)

3D printing based soy protein isolate-flaxseed gum-catechin as a potential strategy to regulate hypertension - Dongbei Shen; Min Zhang; Arun S. Mujumdar; Chunli Li; Jiacong Lin (Food Bioscience, 2025)

Phase transformation of calcium sulfate at mineral-solution interface: An overlooked pathway for selective enrichment of cadmium - Wenjing Li; Guiquan Che; Chunli Wang; Zhihao Zhang; Jing Zhang; Zhang Lin (Journal of Hazardous Materials, 2025)

Subnanometer ultra-thin magnetic nanosheets for highly sensitive magnetic resonance angiography - Kun Liu; Na Yang; Chunmin Bo; Xianglong Zhu; YiFan Fan; Hong Hao; Zhen Jin; Jinhao Gao; Hongyu Lin; Chunli Wang (Chemical Engineering Journal, 2025)

Additive manufacturing technology in the development of easy to swallow and digest foods for the elderly - Dongbei Shen; Min Zhang; Arun S. Mujumdar; Chunli Li; Jiacong Lin (Food Research International, 2025)

Lead-free halide perovskite-based optoelectronic synapse for reservoir computing - Lingling Zhang; Yafei Chen; Shuaifei Mao; Zhenyu Li; Chunli Jiang; Chunhua Luo; Hechun Lin; Jadranka Travas-Sejdic; Hui Peng (Chemical Engineering Journal, 2025)

Photoelectric synaptic device based on Cu2ZnSnS4/ZnO heterojunction for non-volatile vision memory - Shuaifei Mao; Jiantong Ge; Lingling Zhang; Yannan Dai; Sheng Jiang; Yafei Chen; Chunli Jiang; Chunhua Luo; Bobo Tian; Hechun Lin; Hui Peng; Chun-Gang Duan (Chemical Engineering Journal, 2024)

Rationally engineered core-shell structured Fe0@FeS towards the efficacious synergistic Cr(VI) and Ni(II) removal - Zishen Lin; Chunli Zheng; Zhenxing Wang; Yuanzhe Peng; Guoqing Geng; Aibin Zhu; Chi He (Chemical Engineering Journal, 2024)

Plant regeneration in the new era: from molecular mechanisms to biotechnology applications - Chunli Chen; Yuxin Hu; Momoko Ikeuchi; Yuling Jiao; Kalika Prasad; Ying Hua Su; Jun Xiao; Lin Xu; Weibing Yang; Zhong Zhao; Wenkun Zhou; Yun Zhou; et al. (Science China Life Sciences, 2024)

Microbial strategies for effective hexavalent chromium removal: A comprehensive review - Shilin Zha; Ao Yu; Zhongbing Wang; Qi Shi; Xunniu Cheng; Chunli Liu; Chunjian Deng; Guisheng Zeng; Shenglian Luo; Zongwen Zhao; Lin Zhou (Chemical Engineering Journal, 2024)

Enhanced extraction of heavy metals from gypsum-based hazardous waste by nanoscale sulfuric acid film at ambient conditions - Wenjing Li; Chunli Wang; Guiquan Che; Min Su; Zhihao Zhang; Weizhen Liu; Zhang Lin; Jing Zhang (Journal of Hazardous Materials, 2024)

Effects of microtopography on soil microbial communities in alpine meadows on the Qinghai-Tibetan Plateau - Xinwei Li; Xilai Li; Yan Shi; Shoujing Zhao; Jiale Liu; Yinyi Lin; Chunli Li; Chunhui Zhang (CATENA, 2024)

Ultralow-Concentration (0.1M) Electrolyte for stable bulk alloy (Sn, Bi) anode in Sodium-ion battery via Regulating Anions Structure - Changting Chu; Lin Zhou; Yong Cheng; Xuxu Wang; Limin Chang; Ping Nie; Chunli Wang; Limin Wang (Chemical Engineering Journal, 2024)

Effect and mechanism of kaolinite loading amorphous zero-valent iron to stabilize cadmium in soil - Jieling Ren; Chunli Zheng; Yingying Yong; Zishen Lin; Aibin Zhu; Chi He; Hua Pan (Science of The Total Environment, 2023)

Dual-modal artificial synapse based on a lead-free halide Cu2AgBiI6 for image processing and information encryption - Shuaifei Mao; Mingqing Cui; Sheng Jiang; Pengfei Zhao; Jie Lao; Chunli Jiang; Chunhua Luo; Bobo Tian; Hechun Lin; Jadranka Travas-sejdic; Hui Peng; Chun-Gang Duan (Chemical Engineering Journal, 2023)

Biomineralization behavior and mechanism of microbial-mediated removal of arsenate from water - Xiang Liu; Wanqing Ren; Miao Lin; Xuejun Tan; Chunli Wan (Environmental Research, 2023)

Tannic acid exerts antifungal activity in vitro and in vivo against Alternaria alternata causing postharvest rot on apple fruit - Haixia Wang; Lin Fu; Chunli Li; Xinlu Zhang; Kpadonou Essedolo Narcisse; Haishi Qi; Chuanyu Han; Xiangyu Wang; Hongbin Ma; Chunyu Zhu; Fangliang Zheng (Physiological and Molecular Plant Pathology, 2023)

MiR-361-3p alleviates cerebral ischemia–reperfusion injury by targeting NACC1 through the PINK1/Parkin pathway - Xihong Ye; Hua Song; Huimin Hu; Chunli Zhou; Qinyi Chen; Lin Hong; Min Huang; Hongfei Zhu (Journal of Molecular Histology, 2022)

The nucleic acid positive rate and genotype distribution of human cytomegalovirus in human milk banks in China - Xiaoyu Min; Lin Wang; Aili Cui; Chunli Zhang; Dan Wang; Ying Liu; Zhenghong Li; Wenbo Xu (Archives of Virology, 2020)

Indoor/outdoor pollution level and personal inhalation exposure of polycyclic aromatic hydrocarbons through biomass fuelled cooking - Guofeng Shen; Yanyan Zhang; Siye Wei; Yuanchen Chen; Chunli Yang; Pengchuan Lin; Han Xie; Miao Xue; Xilong Wang; Shu Tao (Air Quality, Atmosphere & Health, 2014)

Contamination and distribution of parent, nitrated, and oxygenated polycyclic aromatic hydrocarbons in smoked meat - Yuanchen Chen; Guofeng Shen; Shu Su; Huizhong Shen; Ye Huang; Tongchao Li; Wei Li; Yanyan Zhang; Yan Lu; Han Chen; Chunli Yang; Nan Lin; et al. (Environmental Science and Pollution Research, 2014)

Transcriptional and Functional Studies of a Cd(II)/Pb(II)-Responsive Transcriptional Regulator(CmtR) from Acidithiobacillus ferrooxidans ATCC 23270 - Chunli Zheng; Yanjun Li; Li Nie; Lin Qian; Lu Cai; Jianshe Liu (Current Microbiology, 2012)

K30, H150, and H168 Are Essential Residues for Coordinating Pyridoxal 5′-Phosphate of O-Acetylserine Sulfhydrylase from Acidithiobacillus ferrooxidans - Chunli Zheng; Li Nie; Lin Qian; Zhilou Wang; Guizhen Liu; Jianshe Liu (Current Microbiology, 2010)